The Traditional Game of Kuntulan Review from The Cognitive, Affective and Psychomotor Aspects in The Physical Education Learning - Astuti, Widy; Pramono, Harry; Rumini, Rumini (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The background of this research is the return of the traditional kuntulan game that is played in PJOK learning at school. The application of this game is assessed through three aspects of assessment, namely cognitive, affective and psychomotor aspects. The objectives of this study are: (1) to analyze the role of cognitive aspects in traditional kuntulan games, (2) to analyze the role of affective aspects in traditional kuntulan games, (3) to analyze the role of psychomotor aspects in traditional kuntulan games in learning physical education. This study uses a qualitative descriptive design approach. The data sources of this research are Expert Lecturers, Physical Health Teachers and Students of SMPN 2 Warungasem. Data collection techniques using observation, interviews and documentation. Data analysis consists of 4 interacting components, namely, data collection, data reduction, data display and conclusion. The results of the cognitive aspect research have 4 indicators, namely history, development, form of the game, and the sequence of movements of the kuntulan game, the total score is 1733, the average is 72.21. Students who score more than 70 are 41 students and less than 70 are 7 students. There are 6 affective indicators in which the total score is 1970, the average is 82. Students who score more than 70 are 41 students and less than 70 are 7 students. Psychomotor there are 8 indicators that the total score is 1331, the average is 70. Students who get a score of more than 70 are 28 students and less than 70 are 20 students. The conclusion of the research on the cognitive aspects of students can master well. In the Affective Aspect, students can bring out the affective character well. On the psychomotor aspect of students in playing kuntulan games moderately.